Development of an interactive teaching-learning technique of mathematics based on the EIF technique for the primary schools - Ahmad, Ab. Rahman; Aris, Baharudin (Faculty of Computer Science and Information System, 2004)
The advancement in computer hardware and software provide a greater impact on the educational technology. The computer is now widely used as a new form of teaching and learning strategy to complement the traditional teaching methods. This research is devoted to the development of a multi-media education for Mathematics KBSR Year 2,using the new syllabus from the Ministry of Education. An alternative teaching and learning strategy comprised of three stages i.e., Explain, Instruct and Facilitate (EIF)has been proposed to the existing approach in education. By this strategy, the teaching and learning becomes more structured and interactive. Students not only be exposed to the introduction of new topics and its practices, but also generate creativity by formulating their own ideas to approach problems. This technique is now incorporated to the multi-media computer facilities in order to make the learning process more fun and enjoyable. This system is developed using Microsoft Visual Basic and other sounds and graphics software running under Windows platform. Through sub sequence research and survey, the product is expected to gain a large acceptance among individuals and schools throughout Malaysia.